The burden of mental illness : an emerging global disaster / Mohd Razali Salleh. - Salleh, Mohd Razali (Universiti Teknologi MARA Cawangan Selangor, 2018)
The global burden of disease (GBD) has shifted from communicable to non-communicable diseases, and from premature death to years live with disabilities (YLDs) over the past 30 years. Mental and substance use disorders constitute a major component in the scenario of the global health with a significant impact on the global burden of disease, especially in the developing countries. The 1990 GBD study listed depression as the fourth common cause of global burden of disease; while lower respiratory infections, diarrheal diseases and conditions arising during perinatal period are top in the list. In GBD 2000 study depressive disorders climbed to the third place, however still behind lower respiratory infections and diarrheal diseases. The subsequent 2010 GBD study ranked depression in the second place of the global disability burden, and are also considered as a major contributor to the burden of suicide and ischaemic heart disease. The WHO predicted that depressive disorders will be the leading cause of global burden in 2030.